Pengaruh Pemberian Pupuk Organik Padat Terhadap Pertumbuhan Rumput Bede (Brachiaria decumbens) - Emanuel; Ni Ketut Etty Suwitari; I Gusti Ayu Dewi Seri Rejeki (Fakultas Pertanian, Universitas Warmadewa, 2025)
Bede grass (Brachiaria decumbens) is a plant that has good quality for green fodder. This can be seen from the growth rate, production and nutritional content contained therein. This study aims to determine the effect of providing solid organic fertilizer on the growth of Bede grass (Brachiaria decumbens) and to determine the effect of providing solid organic fertilizer with different doses on the growth of Bede grass (Brachiaria decumbens). The design used in this study was a randomized block design (RAK) with 5 treatments and 3 replications. The treatments used were P0 = Grass without providing solid organic fertilizer, P1 = Grass with providing 10 tons/ha of solid organic fertilizer, P2 = Grass with providing 20 tons/ha of solid organic fertilizer, P3 = Grass with providing 30 tons/ha of solid organic fertilizer, P4 = Grass with providing 40 tons/ha of solid organic fertilizer. From the results of the study, the provision of solid organic fertilizer had no significant effect (P>0.05) on all growth and production parameters of Bede grass (Brachiaria decum bens), except for the production of fresh leaf weight, which showed a significantly different effect (P<0.05). This shows that the application of solid organic fertilizer with various doses has not provided a significant effect on the vegetative growth of plants. The provision of solid organic fertilizer with different doses did not have a significant effect (P>0.05) on the growth of Brachiaria decumbens. However, the provision of solid organic fertilizer with a dose of 30 tons/ha has the potential to provide the best growth and production results compared to other doses. The researcher suggests that further research is needed to take into account environmental factors such as light intensity and soil conditions to better understand the effect of solid organic fertilizer on Bede grass (Brachiaria decumbens) and the use of a dose of solid organic fertilizer of 30 tons/ha can be considered because it shows a tendency for the best results even though it has no significant effect.